The Symbolic Meaning of Food in the Manggulan Nyambung Tuwuh Manten Tradition in Betak Village - Khamimiya, Aza Rifda; Sudrajat, Arief (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
This study explains the symbolic meaning of the existence of food in the Manggulan nyambung tuwuh manten tradition. The method used is qualitative as an approach and symbolic interaction theory as an analytical knife to describe human interaction with the meaning of symbols that exist on an object. The data used are primary data through observation, in-depth interviews with traditional leaders, and documentation. Then the data is supported by secondary data from literature studies. The data obtained was then analyzed through three stages, namely data reduction, data presentation and drawing conclusions. The research is located in Betak Village, Kalidawir District, Tulungagung Regency. The results of this study are the types and meanings of food, namely ambengan, keleman, gedang setangkep, strong buceng, sega golong, kembang setaman, jenang abang and jenang sengkala and sego punar. The meaning of the existence of these foods is as an expression of gratitude and freedom from danger for people who have needs. The Betak Village community in carrying out the Manggulan tradition has undergone changes so that the sacredness of this tradition is reduced. This can happen because of the influence of modernization